Melatonin, Zinc, and Vitamin C: Potential Adjuvant Treatment for COVID-19 Patients - Borges, Leandro; Gennari-Felipe, Matheus; Dias, Beatriz Belmiro; Hatanaka, Elaine (Frontiers in Nutrition, 2022)
The use of nutraceutical approaches may regulate the immune system, performing a potential strategy to contain the worst outcomes of COVID-19. We reviewed the current evidence surrounding nutritional/nutraceutical approaches for the therapy in COVID-19 patients. We searched the PubMed database to report randomized controlled trials (RCTs) and observational research that used melatonin, vitamin C, or zinc supplementation as an intervention for COVID-19 treatment. To date, we found only three concluded studies that assessed zinc supplementation and melatonin therapy in COVID-19 patients but with inconclusive data, relatively small sample size, and early termination of the trial. On the other hand, vitamin C therapy appears to reduce hyperinflammation and improve the oxygen support status of COVID-19 patients. However, a large part of this research involves pilot trials and there are still conflicting data regarding mortality rate, mechanical ventilation, and duration of symptoms of COVID-19 patients. Melatonin, zinc, and vitamin C supplementation should be investigated further on the nutritional status-immune response, and data from ongoing trials are needed to understand these molecules as a therapy strategy in COVID-19 patients.